Isolation and Characterization of Biosurfactant-producing Bacteria from Ternary Effluent within Maiduguri Metropolitan Council (Asian Journal of Plant Biology, 2023)
Almost all surfactants currently in use are chemically derived from petroleum. However, the diversity of biosurfactants, environment friendly characteristics, the possibility of their production through fermentation and their potential applications in areas such as environmental protection, surface crude oil recovery, health care and food processing industries, has made its interest steadily increasing in recent years. This research is targeted towards the isolation of indigenous biosurfactant producing bacteria from the local tanneries in Maiduguri. Physico – chemical parameters such as temperature and pH of all samples were tested at the site of collection, while others such as Biochemical Oxygen Demand (BOD), Desolved Oxygen (DO) and Electrical Conductivity (EC) were tested ex – situ. Simple and selective microbiological media were used for the isolation. A total of ten (10) different bacterial isolates were obtained from the eighteen (18) samples tested. Identification of the isolates was achieved through morphological and Biochemical analysis. The isolates obtained included Providencia rettgeri, Salmonella enterica, Enterobacter cancerogenus, Leminorella richardii, Bacillus licheniformis, B. niacini, Paenibacillus residui, Proteus mirabilis, Lysinibacillus massiliensis and L. fusiformis. Of the ten (10) isolates obtained, only seven (7) were found positive for biosurfactant production. They incuded P. rettgeri, E. cancerogenus, L. richardii, B. niacini, P. residui, L. massiliensis and L. fusiformis, of which L. fusiformis showed the highest emulsification activity of 25% at 4cm emulsion height. The results suggest that the Majema tannery effluents harbour biosurfactant - producing bacteria. Thus, tannery effluents can be possibly remediated using the biosurfactants and bacteria producing the biosurfactants.
Keywords: Isolation; Characterization; Tannery; Biosurfactant; L. fusiformis